2019
DOI: 10.1101/596858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Achronopresence: how temporal visuotactile and visuomotor mismatches modulate embodiment

Abstract: The loss of body ownership, the feeling that your body and its limbs no longer belong to you, presents a severe clinical condition that has proven difficult to study directly. We here propose a novel paradigm using mixed reality to interfere with natural embodiment using temporally conflicting sensory signals from the own hand. In Experiment 1 we investigated how such a mismatch affects phenomenological and physiological aspects of embodiment, and identified its most important dimensions using a principle comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 75 publications
4
13
0
Order By: Relevance
“…In keeping with previous findings [15,[48][49][50][51][52][53][54], we observed that the disintegration of visual, tactile and proprioceptive signals from participants' own hand resulted in a reduction in perceived ownership over that hand (S3). This was observed for both VT incongruent VP match and VT incongruent VP mismatch conditions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In keeping with previous findings [15,[48][49][50][51][52][53][54], we observed that the disintegration of visual, tactile and proprioceptive signals from participants' own hand resulted in a reduction in perceived ownership over that hand (S3). This was observed for both VT incongruent VP match and VT incongruent VP mismatch conditions.…”
Section: Discussionsupporting
confidence: 91%
“…We must consider the general lack of changes in skin conductance response to threat, our objective measure of changes in body ownership, following multisensory disintegration. Whilst this is in keeping with another recent study using a multisensory disintegration paradigm [53], it is in contrast to Gentile et al [48], who observed reductions in skin conductance response to threat in conditions inducing reductions in the sensation of own hand ownership. It is possible that this stems from differences between our paradigm and the one employed by Gentile et al [48].…”
Section: Experimental Limitationssupporting
confidence: 86%
See 2 more Smart Citations
“…These strong phenomenal descriptions however were not in line with the physiological measures, which might indicate that the effect was not as strong as in previously described multisensory illusions, but might also be linked to accumulating evidence not replicating the link between phenomenal alterations of the bodily self and physiological measures such as temperature (de Haan et al, 2017;Roel Lesur et al, 2020). Yet, in consistency with previous finings for experimentally induced autoscopy (Lenggenhager et al, 2007(Lenggenhager et al, , 2009Noel et al, 2015), we found changes in the location of self-identified extracorporeal cues.…”
Section: Discussionmentioning
confidence: 57%